A Handful of Stars - Lord, Cynthia (New York : Scholastic Press, 2015)
When her blind dog slips his collar, twelve-year old Lily meets Salma Santiago, a young Hispanic girl whose migrant family are in Maine for the blueberry-picking season, and, based partly on their mutual love of dogs, the two forge a friendship while painting bee boxes for Lily's grandfather--but as the Blueberry Queen pageant approaches Lily and Selma are confronted with some of the hard truths of prejudice and migrant life.
Keywords: Children of migrant laborers -- Juvenile fiction; Hispanic American children -- Juvenile fiction; Blind dogs -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Friendship -- Juvenile fiction; Blueberry industry -- Juvenile fiction; Migrant labor -- Fiction; Hispanic Americans -- Fiction; Blind dogs -- Fiction; Dogs -- Fiction; Grandparents -- Fiction; Friendship -- Fiction; Blueberry industry -- Fiction; Maine -- Juvenile fiction; Maine -- Fiction